Corporate Governance and its Effects on the Financial Performance of Commercial Banks in Nepal - Hada, Maheshwar Lal (Journal of Economics and Management, 2023)
This current study aims to explore the impact of corporate governance on the financial performance of commercial banks in Nepal. Although there were many researches made on the topic “Impact of Corporate Governance on Financial Performance,” However there is only a handful of research found in respect of commercial banks in Nepal. This study tried to fill the gap by studying exclusively in the banking industry of Nepal. The financial performance is measured through Return on assets (ROA) as the dependent variable, and corporate government variables are measured through the percentage of foreign directors in the board, board size, board independence, and board diligence as independent variables. Panel data analysis was used for the study covering the period from 2016/017 to 2020/021 using both descriptive statistic, correlation, multiple regression and t-test to examine the governance practices and their effect in the financial performance of commercial banks in Nepal. The empirical results demonstrated that board diligence (DB) has a positive significant impact on ROA. The result also indicates that there is an insignificant impact of other variables (FD, BI, BS) on ROA of commercial banks in Nepal.